The New Public Management as a Mechanism to Combat Administrative Corruption In Algeria - معيزة , نوال; شعباني, مجيد (Finance and Business Economies Review, 2021)
this article aims to present Algeria's experience in combating administrative corruption, during the last two decades, as the phenomenon has worsened terribly in all sectors of society, and its effects have become visible in a way that cannot be hidden to the point where the deviant behavior of employees has become the natural and acceptable form of conducting business in public organizations or The public had to come together in order to combat administrative corruption and highlight the role of the new managment public as a mechanism to combat the phenomenom within the pillars of organizations in which corruption has spread, especially since the public organizations in Algeria, whether economic or administrative, have failed in all reform attempts and they are known for mismanagement, extravagance and corruption; despite all the legal and economic strategies adopted to combat administrative